Stretched to the limit; can a short pelagic larval duration connect adult populations of an Indo‐Pacific diadromous fish (Kuhlia rupestris)?. Issue 6 (7th January 2013) - Feutry, P.; Vergnes, A.; Broderick, D.; Lambourdière, J.; Keith, P.; Ovenden, J. R.
Abstract Freshwater species on tropical islands face localized extinction and the loss of genetic diversity. Their habitats can be ephemeral due to variability in freshwater run‐off and erosion. Even worse, anthropogenic effects on these ecosystems are intense. Most of these species are amphidromous or catadromous (i.e. their life cycle includes a marine larval phase), which buffers them against many of these effects. A long pelagic larval duration (PLD) was thought to be critical to ensure the colonization and persistence in tropical islands, but recent findings indicated that several species with short PLDs are successful in those ecosystems. To test the potential of a short PLD in maintaining genetic connectivity and forestalling extirpation, we studied Kuhlia rupestris, a catadromous fish species with an extensive distribution in the western Pacific and Indian Oceans. Using a combination of molecular genetic markers (13 microsatellite loci and two gene regions from mtDNA) and modelling of larval dispersal, we show that a short PLD constrains genetic connectivity over a wide geographical range. Molecular markers showed that the short PLD did not prevent genetic divergence through evolutionary time and speciation has occurred or is occurring. Modelling of larvae dispersal suggested limited recent connectivity between genetically homogeneous populations across the Coral Sea. However, a short PLD can maintain connectivity on a subocean basin scale. Conservation and management of tropical diadromous species needs to take into account that population connectivity may be more limited than previously suspected in those species.